Osoby pełno- versus niepełnosprawne – infrahumanizowanie studentów z niepełnosprawnością (studium przypadku) - Bełza-Gajdzica, Magdalena (Kultura-Społeczeństwo-Edukacja, 2020)
Bełza-Gajdzica Magdalena, Able-bodied vs. disabled people – infrahumanisation of students with disabilities (a case study). Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 71–83, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.5. The article discusses the phenomenon of infrahumanisation in academic relations between able-bodied people (both students and academics) and students with disabilities. The main goal of the article is to show that infrahumanisation may make it difficult for young people with disabilities to build their capital for the future in the form of interpersonal relations. The paper uses Arnold van Gennep’s concept of the rite of passage as a model of entering adulthood, and focuses specifically on the stage of university education as the one which completes the transition into adulthood, and marks the beginning of a “normal” life (i.e. one consistent with social expectations). The phenomenon of infrahumanisation shown here on various levels of academic life disrupts this process, and may hinder the inclusion/integration of disabled people into society. The relations between disabled students and non-disabled people who are part of the academic community in which the students operate may, however, also bridge the distance between the two groups, and thus contribute to paving the way to a respectful society, i.e. the way of equality.